2021
DOI: 10.1007/s10926-021-09978-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Employer in Supporting Work Participation of Workers with Disabilities: A Systematic Literature Review Using an Interdisciplinary Approach

Abstract: Purpose There is growing awareness that the employer plays an important role in preventing early labor market exit of workers with poor health. This systematic review aims to explore the employer characteristics associated with work participation of workers with disabilities. An interdisciplinary approach was used to capture relevant characteristics at all organizational levels. Methods To identify relevant longitudinal observational studies, a systematic literature search was conducted in PubMed, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…The importance of providing work accommodations is in line with previous studies. A recent systematic review on the role of the employer in supporting work participation by workers with disabilities, gave moderate to strong evidence of the benefits of work accommodations like adjusted work schedules, provision of equipment, and modified work activities to help workers to return to work, and to stay employed after the onset of work disability [29]. Informal instrumental support, as by coworkers who are willing to take over work tasks, has been identified as a substantial type of work accommodation, both vital and easy to implement during the first phase of sick leave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of providing work accommodations is in line with previous studies. A recent systematic review on the role of the employer in supporting work participation by workers with disabilities, gave moderate to strong evidence of the benefits of work accommodations like adjusted work schedules, provision of equipment, and modified work activities to help workers to return to work, and to stay employed after the onset of work disability [29]. Informal instrumental support, as by coworkers who are willing to take over work tasks, has been identified as a substantial type of work accommodation, both vital and easy to implement during the first phase of sick leave.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted thematic analyses by developing a systematic coding process to identify themes and patterns in the data. The thematic coding scheme was based on themes retrieved from a previous systematic review conducted by our team [29]; from an article on the "Reasonable Accommodation Factor Survey" [30]; and on additional codes retrieved from the transcripts. Memos made during and directly after the interviews helped to identify the saturation point of the themes.…”
Section: Methodsmentioning
confidence: 99%
“…People with mental illnesses are limited in how much they can manage themselves and, therefore, require understanding and support, such as through consultation with others, to continue working. As demonstrated in our previous conceptual analysis [ 14 ], a workplace that believes in the employees’ abilities, has a support system, and a sense of security is an essential prerequisite for continued employment [ 26 , 27 , 28 ]. For example, Factor 3, adjustments in the environment, was characterised by people with mental illnesses appealing to supervisors and colleagues to adjust their environment to continue working.…”
Section: Discussionmentioning
confidence: 99%
“…The (lack of) findings regarding factors more specifically related to the work situation were not expected since the intervention group received the DAP intervention, supposedly targeting a successful RTW process. The DAP intervention actively involves the manager of the individual with chronic pain in the RTW process [ 31 ], and a good relationship and collaboration between the manager and the employee has previously been highlighted as important for a successful RTW [ 25 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In two recent studies of ours, investigating the patient’s perspective [ 51 ] and the manager’s perspective (not yet published) when participating in the DAP, we found that the intervention was perceived to promote their relationship and collaboration.…”
Section: Discussionmentioning
confidence: 99%